Splenectomy in Chanrain-Dorfman syndrome - Majd Hawat; Lina Khouri; Mohammad Almansour (Elsevier, 2021)
Chanrain-Dorfman syndrome (CDS; MIM 275630) is multisystem lipidosis where the triglyceride accumulate in the leukocytes and other organs results in different clinical findings in skin, liver, and muscle plus ocular abnormalities. This syndrome also is known as Neutral Lipid Storage Disease with Ichthyosis. We describe the first known report of splenectomy in CDS patient. The child was diagnosed with congenital ichthyosis at birth and treated locally. When he became 7 years old he suffered from blurred vision in both eyes and found to have Splenomegaly after we put our diagnosis we did the splenectomy surgery due to pancytopenia and in 3 month of follow up the Haemoglobin and WBCs and RBCs showed great improvement. This case suggests that splenectomy may be a good treatment for CDS patients when develop hypersplenism and pancytopenia.